Evaluation of native mycorrhizae in plantain crop (musa aab simmonds) in nursery phase (2012)
The aim of the present research was to evaluate the effect of three vesicular arbuscular Mycorrhi+al native genera application on growth of Hartón plantain plants in nursery stage. The strains were obtained at the Universidad de Córdoba from the Plant Pathology Laboratory collection, which were isolated from plantain crops in Lorica, Las Córdobas and  San Bernardo del Viento. A completely randomized experimental design with six treatments DTE was used: Glomus sp. (T1), Acaullospora sp. (T2), Scutellospora sp. (T3), a genera combination of Glomus, Acaullospora and Scutellospora (T4), a chemical treatment (diammonium phosphate, DAP, T5E and absolute control DT6E, with ten replicates per treatment. Results showed that a greatest quantity of spores were obtained and higher infection percentage with the combination of mycorrhizae genera DT4E, followed by TY, T3 and T2 treatments. Besides the above mentioned, with the combination of mycorrhizal genera, they were obtained significant difference compared with other treatments in regard to pseudostem diameter, leaf area ratio:fresh and dry weight of root. Regarding to leave area and root length, T5 treatment showed the higher measurements.